2019
DOI: 10.1088/1674-1137/43/5/053103
|View full text |Cite
|
Sign up to set email alerts
|

Spectral hardening of cosmic ray protons and helium nuclei in supernova remnant shocks *

Abstract: The observed hardening of the spectra of cosmic ray protons and helium nuclei is studied within the model of nonlinear diffusive shock acceleration of supernova remnants (SNRs). In this model, the injected particles with energies below the spectral " knee” are assumed to be described by two populations with different spectral indexes around 200 GeV. The high-energy population is dominated by the particles with energies above 200 GeV released upstream of the shock of SNR, and the low-energy population is attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…These results indicate that their internal protons can be accelerated to the order of 10 2 TeV, which is close to the particle acceleration limit of current SNRs in the Milky Way (Aharonian et al 2007(Aharonian et al , 2011Morlino & Caprioli 2012). Berezhko et al (2003) analyzed the X-ray data of SN 1006 from Chandra observations and confirmed the magnetic field amplification, which can effectively accelerate nuclear CRs in SNRs to TeV or PeV levels (Tang et al 2013;Lin et al 2019). Similar to the SNRs in the Milky Way, if the SBGs contain numerous SNRs and the energy of CR particles in these SNRs can be accelerated to the 10 2 TeV level, then there should be a strong magnetic field amplification near the shock surface in SNRs (Lin et al 2019).…”
Section: Likely Protonic Acceleration Limit Within Sbgssupporting
confidence: 62%
“…These results indicate that their internal protons can be accelerated to the order of 10 2 TeV, which is close to the particle acceleration limit of current SNRs in the Milky Way (Aharonian et al 2007(Aharonian et al , 2011Morlino & Caprioli 2012). Berezhko et al (2003) analyzed the X-ray data of SN 1006 from Chandra observations and confirmed the magnetic field amplification, which can effectively accelerate nuclear CRs in SNRs to TeV or PeV levels (Tang et al 2013;Lin et al 2019). Similar to the SNRs in the Milky Way, if the SBGs contain numerous SNRs and the energy of CR particles in these SNRs can be accelerated to the 10 2 TeV level, then there should be a strong magnetic field amplification near the shock surface in SNRs (Lin et al 2019).…”
Section: Likely Protonic Acceleration Limit Within Sbgssupporting
confidence: 62%
“…The measurement of the proton and light primary nuclei fluxes [1] does not follow a single power law and progressively hardens at high rigidities, with an increase of the spectral index above 200 GV. Many models have been proposed to explain this spectral feature according to distinct contributions: different acceleration mechanisms at source [2][3][4], propagation effects [5][6][7], and local sources [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…TeV, which is close to the particle acceleration limit of current SNRs in the Milky Way (Aharonian et al 2007(Aharonian et al , 2011Morlino & Caprioli Morlino2012). Berezhko et al (2003) analyzed the X-ray data of SN 1006 from Chandra observation and confirmed the magnetic field amplification, which can effectively accelerate nuclear CRs in SNRs to TeV or PeV level (Tang et al 2013;Lin et al 2019). Similar to those SNRs in the Milky Way, if the SBGs contain a large number of SNRs and the energy of CR particles in these SNRs can be accelerated to 10 2 TeV level, then there should have a strong magnetic field amplification near the shock surface in SNRs (Lin et al 2019).…”
Section: Likely Protonic Acceleration Limit Within Sbgsmentioning
confidence: 99%
“…Berezhko et al (2003) analyzed the X-ray data of SN 1006 from Chandra observation and confirmed the magnetic field amplification, which can effectively accelerate nuclear CRs in SNRs to TeV or PeV level (Tang et al 2013;Lin et al 2019). Similar to those SNRs in the Milky Way, if the SBGs contain a large number of SNRs and the energy of CR particles in these SNRs can be accelerated to 10 2 TeV level, then there should have a strong magnetic field amplification near the shock surface in SNRs (Lin et al 2019). If the evolution of CR particles in NGC 253 and M82 are similar to that of SNRs in the Milky Way, then the magnetic field amplification is likely to be a important mechanism for the acceleration of particles inside them to 10 2 TeV level.…”
Section: Likely Protonic Acceleration Limit Within Sbgsmentioning
confidence: 99%